Энергетика пищевых нанотехнологий - Бурдо, О. Г.; Бандура, В. Н.; Ружицкая, Н. В.; Яровой, И. И. (НТУ "ХПИ", 2012)
The food nanotechnologies development directions have been considered in the paper. Classification of food raw nanoscale objects has been given. The analysis of new combined wave barodiffusion tecnologies based transport processes mechanisms has been given. Energy aspects of using these technologies in extraction and product dehydration have been considered. The examples of wave and barodiffusion technologies practical use in coffee, cognac production, grain drying, microorganisms inactivation, water demineralization have been provided.
Keywords: нанотехнологии; пищевая промышленность; микроорганизмы; бародиффузионный механизм; обезвоживание; экстрактор